The Effect of Revenue and Operating Costs on Net Income at PT. Fast Food Indonesia Tbk 2017-2021 - Setia Zebua, Yenima Ingat; Noor Sembiring (Journal of Accounting and Finance Management, 2023)
The success of the company can be shown by looking at the growth of net income and revenue as well as how the company in managing operations and finally can get a clear picture of the level of success of the company. This study aims to draw conclusions whether there is evidence that Total Revenue and Operating Costs affect Net Income. In this study the method used is quantitative, the results of this research are processed using SPSS 25. The results of this study indicate that Total Revenue and Operating Expenses have a positive and significant effect on Net Income.